2021
DOI: 10.1007/s00401-021-02313-3
|View full text |Cite
|
Sign up to set email alerts
|

LRP10 interacts with SORL1 in the intracellular vesicle trafficking pathway in non-neuronal brain cells and localises to Lewy bodies in Parkinson’s disease and dementia with Lewy bodies

Abstract: Loss-of-function variants in the low-density lipoprotein receptor-related protein 10 (LRP10) gene have been associated with autosomal-dominant Parkinson’s disease (PD), PD dementia, and dementia with Lewy bodies (DLB). Moreover, LRP10 variants have been found in individuals diagnosed with progressive supranuclear palsy and amyotrophic lateral sclerosis. Despite this genetic evidence, little is known about the expression and function of LRP10 protein in the human brain under physiological or pathological condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(62 citation statements)
references
References 96 publications
5
57
0
Order By: Relevance
“…LRP10 is a single-pass transmembrane protein and a member of a subfamily of LDL receptors. Grochowska et al discovered that LRP10 expression was high in non-neuronal cells but undetectable in neurons, and that it was present in the trans-Golgi network, plasma membrane, retromer, and early endosomes in astrocytes [ 107 ]. They suggested that LRP10-mediated pathogenicity involves the interaction of LRP10 and SORL1 in vesicle tracking pathways, as they were shown to co-localize and interact, and that disturbed vesicle trafficking and loss of LRP10 function were crucial in the pathogenesis of neurodegenerative diseases [ 107 ].…”
Section: Recently Described Parkinson’s Disease Genesmentioning
confidence: 99%
“…LRP10 is a single-pass transmembrane protein and a member of a subfamily of LDL receptors. Grochowska et al discovered that LRP10 expression was high in non-neuronal cells but undetectable in neurons, and that it was present in the trans-Golgi network, plasma membrane, retromer, and early endosomes in astrocytes [ 107 ]. They suggested that LRP10-mediated pathogenicity involves the interaction of LRP10 and SORL1 in vesicle tracking pathways, as they were shown to co-localize and interact, and that disturbed vesicle trafficking and loss of LRP10 function were crucial in the pathogenesis of neurodegenerative diseases [ 107 ].…”
Section: Recently Described Parkinson’s Disease Genesmentioning
confidence: 99%
“…Neural progenitor cells were generated via inhibiting BMP and TGFβ signaling (dual-SMAD) and stimulation of WNT and SHH signaling with small molecules according to published protocols (Grochowska et al, 2021; Reinhardt et al, 2013) with few modifications. iPSCs grown in feeder-free conditions (StemFlex ™ in combination with Geltrex ™ ) were detached from the plates using the Versene solution.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, however, the role of astrocytes in the neurodegenerative processes gained more attention. Studies have shown that genes known to cause inherited forms of PD are highly expressed in astrocytes and play vital roles in astrocyte function (Bandopadhyay et al, 2004a; Bandopadhyay et al, 2004b; di Domenico et al, 2019; Grochowska et al, 2021; Kim et al, 2016; Kim et al, 2013; Qiao et al, 2016; Strokin et al, 2012). Moreover, in PD, astrocytes can acquire a neurotoxic phenotype, enhance neurodegeneration and thus form a target for therapeutic intervention (Liddelow et al, 2017; Miyazaki and Asanuma, 2020; Schonhoff et al, 2020; Yun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Genes involved in the pathology of neurodegenerative diseases such as AD and ALS have been reported to be associated with PD-associated genes. For example, the LRP10 (Lipoprotein Receptor-Related Protein 10) gene has been recently reported to interact with the AD susceptibility gene SORL1 in a study involving both iPSC-derived cell lines (astrocytes and neurons) and CRISPR/Cas9-edited LRP10 knockout cell lines (HEK293T and HuTu 80) but not a combination of the two (Grochowska et al 2021 ). The study nevertheless provided interesting insights pertaining to the intertwined nature of the genetic architecture of different neuropathological conditions.…”
Section: Parkinson’s Diseasementioning
confidence: 99%